PLATFORM MICROSITE : KONVERGENSI MEDIA PUBLIKASI KEMENTERIA N KEUANGAN RI DI ERA LITERASI DIGITAL - Arifiyanto, Aditya; Utari, Prahastiwi; Rahmanto, Andre Noevi (Master of Communication Science Program, Universitas Diponegoro, 2019)
The development of information technology in recent years has led to various types of information media platforms, including websites and social media. The use of mobile devices has also become a digital trend to access the internet, because this device can be taken anywhere and can be accessed the internet anytime we want. With the presence of technological developments can increase digital literacy in the community. Digital literacy in question is the ability of people to understand and use information from various digital sources. Through this article, the author wants to provide a general description of the Ministry of Finance of the Republic of Indonesia in innovating media convergence in the digital age. The results of this study found the fact that in adapting to the era of digital literacy, the KLI Bureau decided to create a new digital media using the Visual Communication approach for its content using a microsite platform to implement digital convergence media publishing strategies, and named Visual Kemenkeu (VK).